Trash Basket Sensor Notification Using Arduino with Android Application - Adel ALFoudery; Abdulrahman Abdullah Alkandari; Nayfah Mohsen Almutairi (Institute of Advanced Engineering and Science, 2018)
The protection of society and environment from garbage accumulation and its polluting effects is carried by waste management companies, the services provided by these companies are improving life overall quality. By preserving raw materials, proper collecting and elimination of trash have reduced pollution and environmental impact. On the other hand, areas which are suffered from inappropriate negative service appreciate the garbage collector’s valuable efforts. Appropriate garbage collection and management facilities have made a recycling process improvement which caused a reduction in waste generation. Also controlling the released contaminators and pollutants has decreased the impact on landfills and protected the environment from the pollution negative effects. Using mobile and electronic technology to enable waste management companies to finish its work and make it easier for collecting trash in a simple and an easy way. We introduce Trash Sensor Android Application to help waste management companies detect trash levels to collect it and help citizens from undesired odours.